Surface plasmon resonance extension through two-block metal-conducting polymer nanorods - Insub Jung (Nature Portfolio, 2018)
Localized surface plasmon resonance can be exploited for a range of applications, but remains difficult to tailor in metal-organic nanostructures. Here the authors synthesize gold-polypyrrole nanorods and observe a unique extended surface plasmon resonance, which they find to be tunable through doping.